Assessment of ratio of parents preferring general anesthesia in treating children more than 5 years indicated for full mouth rehabilitation - PACKYANATHAN, JERUSHA SANTA; SUBRAMANIAN, EMG; JEEVANANDAN, GANESH (The journal of contemporary issues in business and government, 2021)
When it comes to pediatric patients, the challenge is greater in terms of compliance of the patient, as patient satisfaction is directly related to quality of care while efficiently managing the fear and anxiety of the child. Sometimes, children require treatment for dental caries to be carried out under general anaesthetic (GA) in a hospital setting. Many parents view DGA (Dental general anaesthesia) as an acceptable and often convenient method of treatment to address their child’s oral health needs. The aim of this study was to evaluate parent’s preference for general or local anesthesia in their children’s dental treatments. This was a retrospective study conducted by evaluating data of 1005 patients who underwent invasive treatments in a private dental college between June 2019 to March 2020. To fulfil the inclusion criteria, patients between the age group of 1-17 years (pediatric patients) should have been provided with dental treatment like pulpectomy, SS crowns or strip crowns or FMR etc. The coding was done in MS excel. The data was transferred to a host computer and processed using SPSS software version 20.0 (SPSS Inc., Chicago, IL, USA) by tabulation and graphical illustration. Descriptive statistics was used to study the data collected and to analyse frequency and percentage distribution. Chi square test was used to assess association at 5% significance level (P< 0.05). The results showed that within the limitations of the study, it can be concluded that strong association is seen between age and preference for full mouth rehabilitation under GA. There is however no significant association between gender and preference for full mouth rehabilitation under GA. Of those who underwent FMR under GA, 80% were male and 51% belonged to the 5 years and above age group showing a new trend where patients above 5 years are increasingly opting for treatment under GA.